“The experience of exile determines and leaves a mark forever”: interview with the writer Laura Alcoba (Anclajes, 2020)
The following interview took place in November 2019 from the exchange of emails and conversations in audio format via Whatsapp. The questions aimed above all to establish a precise dialogue around Laura Alcoba’s creative project, editorial politics and translations of the trilogy formed by La casa de los conejos (2008), El azul de las abejas (2015) y La danza de la araña (2018). In this sense, the way in which the three works are linked and propose the construction of an identity not only individual but also collective could be clearly seen.
Keywords: memory; identity; autofiction; trilogy; Laura Alcoba